Determination of water quality status of Way Kuala River, Bandar Lampung City - Sheptiane, Ivena Putri; Delis, Putu Cinthia; Diantari, Rara (Universitas Malikussaleh, 2025)
Way Kuala River is one of the rivers located in urban areas and utilized by various activities around it. Waste from the activities of the surrounding community that was discharged directly into the river will cause a decrease in river water quality. A decrease in water quality can be indicated by changes in physical, chemical, and biological parameters. The purpose of this research is to analyze water quality conditions and determine the water quality status of Way Kuala River, Bandar Lampung City. This research was conducted in November 2024-January 2025 in Way Kuala River, Bandar Lampung City. Sampling was conducted at 3 stations along the Way Kuala River using a direct survey method. Samples were then analyzed in situ, namely direct analysis in the field and ex situ with analysis at the BSPJI Bandar Lampung Laboratory. The data analysis used is STORET, pollution index (IP), and canadian council of ministers of the environment (CCME WQI). The results showed that the condition of Way Kuala River was categorized as polluted. The water quality status of Way Kuala River with STORET tends to be heavily polluted. The water quality status of Way Kuala River with IP tends to be lightly polluted. The water quality status of Way Kuala River with CCME WQI tends to be less polluted. Keywords: CCME WQI; Pollution Index; STORET; Water Quality Status; Way Kuala River